Desenvolvimento e validação de um instrumento para avaliação de curso online na perspectiva do cursista - Pinto, Antonia Cláudia Prado (2023)
With the development of digital technologies in recent years, the world and social relations have changed frighteningly, but only in the early years of the Covid-19 pandemic did society realize how much we should change, especially with regard to education, especially education. way of teaching and learning. As a problem, we reformulate the following guiding question: How can an evaluation instrument improve the quality of an online course and teaching practice? Thus, this research sought to understand the act of evaluating as a mechanism for educational quality, developing and validating an online course evaluation instrument (AVACON) from the perspective of the student, for teacher training in the use of digital technologies in a teacher training course at the Laboratory Digital Educacional, which is a research development center dedicated to scientific production, extension and training, developing a set of pedagogical activities, of a theoretical-practical nature, in face-to-face or distance modalities for continuing education. Considering that many professors sought courses on the use of digital technologies in teaching, especially in the pandemic context, there was a lack of specific instruments to assess the quality of courses. Therefore, the methodological procedures of the referred work were elaborated based on the review of the specific literature of the themes of educational evaluation, teacher formation and distance education, online teaching, remote teaching, resulting in categories, namely: 1-Learning; 2-Materials; 3-Structure; Tools; Methodologies; 4-Human Resources; 5-Evaluative Activities. Two questionnaires were used in the course with answers based on the Likert scale, one about the profile of the participants with eight questions, and the second applied at the end of the course with 20 assertions about the course. The evaluative approach used in this study was the evaluation centered on the perspective of the 654 high school teachers from all over Brazil enrolled in the course on Innovative and Practical Methodologies for Teaching and Learning. The results were recorded and analyzed, not only quantitatively, but also from a qualitative perspective, based on the course participants' responses. The survey revealed the following general results: 1) the suitability of the instrument; 2) their contribution to the institution and the professionals responsible for the classes, selection of media and digital technologies for the course; 3) the relevance of the course; 4) the importance of continuing education; 5) online courses are positive for teacher training; 6) the need for teacher training throughout professional life in digital competence. In view of this, an Educational Product was created, as part of the program requirement, with the website as address: https://avacon-projeto.web.app/. The instrument was inserted on the website with a set of pages that the user could easily access, simply entering through the link provided, navigating through the tabs to appropriate the content and then evaluating the course taken. Finally, from the research, it is inferred that the practice of evaluating contributes significantly to professionals interested in choosing more relevant and quality courses for their training.